Causal association between circulating α-Klotho levels and venous thromboembolism: a two-sample Mendelian randomization study - Yanmin Song; Liping Cao; Hui Long (Thrombosis Journal)
Abstract Background α-Klotho may involve in the occurrence and development of venous thromboembolism (VTE). However, the underlying relationship between circulating α-Klotho levels and VTE is still unclear. Methods This two-sample Mendelian Randomization (MR) study aims to explore the causal associations of circulating α-Klotho levels with different types of venous thromboembolism. Data of exposure and outcomes were extracted from the genome-wide association study (GWAS) of the MRC Integrative Epidemiology Unit (MRC-IEU). The fixed inverse variance weighted (IVW), MR-Egger, MR-Robust Adjusted Profile Score (RAPS) and the weighted-median methods were utilized to investigate the causal associations of circulating α-Klotho levels with different types of VTE. The effect size was expressed as odds ratios (ORs) and 95% confidence intervals (CIs), and the False Discovery Rate (FDR) test was used for correction. The MR scatter plot and leave-one-out test were used for sensitivity analysis. In addition, reverse causal associations were assessed. Results IVW estimates suggested that an elevated circulating α-Klotho level was associated with lower odds of deep vein thrombosis (DVT) of lower extremities (OR = 0.992, 95%CI: 0.986–0.998, P = 0.0074), pulmonary embolism (PE) (OR = 0.474, 95%CI: 0.255–0.881, P = 0.0183), and DVT of lower extremities combined with PE (OR = 0.984, 95%CI: 0.971–0.997, P = 0.0175). However, after the FDR correction, only negatively causal association between circulating α-Klotho level and increased odds of lower-extremity DVT was statistically significant (FDR P = 0.0296). Also, there were no reverse causal associations between the circulating α-Klotho levels and different types of VTE (all P > 0.05). Additionally, both the MR scatter plots and leave-one-out test results showed that these causal associations were relatively robust. Conclusion An elevated circulating α-Klotho levels was associated with lower risk of DVT of lower extremities, PE, and DVT of lower extremities combined with PE, indicating α-Klotho has the potential to act as a target for early screening or treatment for VTE. However, the specific mechanism that α-Klotho influencing the occurrence of VTE still needed further exploration. Graphical Abstract